Philippine medical thesaurus on anatomy body regions in Iluko - Sirios, Cristina Noelle S.; Tarlit, Rodolfo Y. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2003)
This study is a part of the Multilingual Philippine Medical Thesaurus Project, one of the initiatives emanating from the collaborative efforts of the Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila. The partnership started last December 2002 with the signing of the Memorandum of Agreement covering collaborative efforts in medical informatics research. The need for such a unifying thesaurus was the result of the rapid growth of information in the medical field.
The thesaurus was patterned from the Unified Medical Language System (UMLS) of the U.S. National Library of Medicine. The terms, in the study, were gathered from the Medical Subject Headings List (MeSH) for translation to various Philippine languages. One of these languages includes Iluko, the "national languages" of Northern Luzon.
A four-point criteria was used to carry out this research, namely: (1) External validity; (2) Internal validity; (3) Reliability; and (4) Replicability. The population used for this research consisted of five physicians, who served as the key informants in the medical field, and three non-medical professionals. All are native speakers of Iluko. Data gathering included asking these key informants to answer a translation worksheet, where they translated MeSH terms in Iluko. The study also utilized the same ranked dictionary references imposed by a previous study (Simbulan, 2003) for standardization.
Triangulation of data was done in adherence to the Policies and Guidelines Used in Thesaurus Construction by the ISO 5964. Due to the large information at hand, a set of policies and guidelines were adopted from past studies (Siapno, 2003 and Simbulan, 2003) for conformity.
The study was able to translate all 72 MeSH terms in Iluko. The preferred terms primarily came from the medical professionals, non-medical professionals, and the ranked dictionary references, respectively. The study was very satisfactory. This can be credited to the expertise of the informants, which were very competent and knew the language very well.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Subject headings, Ilocano -- Medicine; Subject headings, Ilocano -- Human Anatomy; Ilocano language -- Medical Ilocano